Statistical Damage Constitutive Model for Anhydrite Rock under Freeze–Thaw Cycles Considering the Residual Strength and Postpeak Stress Dropping Rate - Hou, Chao; Jin, Xiaoguang; He, Jie; Li, Hanlin (International Journal of Geomechanics, 2023)
Keywords: Infolettre; Infolettre_Avril_2023; Infolettre_Mai_2023

Investigation of the Multi-Scale Deterioration Mechanisms of Anhydrite Rock Exposed to Freeze–Thaw Environment - Jin, Xiaoguang; Hou, Chao; He, Jie; Dias, Daniel (Materials, 2024)
The deterioration of anhydrite rock exposed to a freeze–thaw environment is a complex process. Therefore, this paper systematically investigated the physical and mechanical evolutions of freeze–thawed anhydrite rock through a series of multi-scale laboratory tests. Meanwhile, the correlation between pore structure and macroscopic mechanical parameters was discussed, and the deterioration mechanisms of anhydrite rock under freeze–thaw cycles were revealed. The results show that with the increase in freeze–thaw processes, the mechanical strength, elastic modulus, cohesion, proportions of micropores (r ≤ 0.1 μm), and PT-Ipore throat (0–0.1 μm) decrease exponentially. In comparison, the mass variation, proportions of mesopores (0.1 μm < r < 1 μm), macropores (r ≥ 1 μm), and PT-II pore throat (0.1–4 μm) increase exponentially. After 120 cycles, the mean porosity increases by 66.27%, and there is a significant honeycomb and pitted surface phenomenon. Meanwhile, as the freeze–thaw cycles increase, the frost resistance coefficient decreases, while the damage variable increases. The correlation analysis between pore structure and macroscopic mechanical parameters shows that macropores play the most significant role in the mechanical characteristic deterioration of freeze–thawed anhydrite rock. Finally, it is revealed that the water–rock expansion and water dissolution effects play a crucial role in the multi-scale damage of anhydrite rock under the freeze–thaw environment.
Keywords: Infolettre; Infolettre_Fevrier_2024

Rainfall-triggered waste dump instability analysis based on surface 3D deformation in physical model test - Li, Hanlin; Jin, Xiaoguang; He, Jie; Xue, Yunchuan; Yang, Zhongping (Journal of Mountain Science, 2024)
Keywords: Infolettre; Infolettre_Ete_2024

Experimental and Numerical Simulation Investigation of the Mechanical Properties of Anhydrite Rock Under Freeze–Thaw Environment - Hou, Chao; Jin, Xiaoguang; Zhai, Shengtian; He, Jie; Lei, Ruide; Dias, Daniel (Geotechnical and Geological Engineering, 2024)
To study the mechanical and cracking modes of anhydrite rock under the freeze–thaw weathering process, the physico-mechanical characteristics and morphology evolutions of anhydrite samples were determined by a series of laboratory tests. Then, a numerical simulation model was established through the PFC2D program, and the types and number of cracks during the uniaxial compression conditions were analyzed. Finally, the distribution of maximum principal stress and shear stress was revealed. The results indicate that as the number of freeze–thaw cycles increases, there is a growth in the mass loss rate and macroscopic damage variables while the uniaxial compression strength and elastic modulus decrease exponentially. Under uniaxial compression stress, the proportion of tensile cracks in the anhydrite model is the highest, followed by tensile shear cracks and compressive shear cracks. As the number of freeze–thaw cycles increases, the proportion of tensile cracks increases exponentially, while the proportion of tensile shear cracks and compressive shear cracks decreases exponentially. Furtherly, it is found that the maximum principal stress and maximum shear stress extreme values decrease exponentially with the increase of freeze–thaw cycles. For example, after 120 cycles, the maximum shear stress at the peak stress point decreased by 47.3%. The research results will promote the comprehension of anhydrite rock geotechnical engineering disaster mechanisms in cold regions.
Keywords: Infolettre; Infolettre_Mai_2024